Pelatihan Dasar Keselamatan Pelayaran (Marine Safety) Untuk SMK Pelayaran dan SMK Perikanan - Pratomo, Sunu Arsy; Haryanto, Haryanto; Kalmah, Kalmah; Kartikawati, Marina; Murti, Bayu; Wa’adulloh, Mu’izzaddin; Sangadji, Ramli; Hamid, Abdul; Diansisti, Annisa; Ikhamuddin, Zihni; et al. (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2026)
Maritime vocational education is required to produce graduates who are not only skilled in operating ships but also have ingrained discipline and a safety culture. This Community Service (PkM) activity is exclusively dedicated to refreshing the technical competencies of Basic Sea Survival for teachers at Maritime and Fisheries Vocational High Schools (SMK). The main target audience consisted of 34 individuals, detailing 22 vocational teachers (SMK N 2 Rembang, SMK N 1 Jepara, SMK Pelayaran Nasional Purwokerto, SMK N 10, and SMK Pelayaran Puring Kebumen) assisted by 12 cadets acting as peer facilitators. Utilizing the Participatory Action Learning System (PALS) method, the training was conducted simultaneously and continuously without breaks (coffee breaks) to simulate the pressure and focus required in a real maritime emergency. The main intervention strictly focused on water survival techniques, covering understanding of SOLAS and STCW regulations, proper life jacket usage (donning), safe water entry procedures, and body temperature retention formations against hypothermia (grouping/huddle). Evaluation results confirmed a massive leap in participants’ skills, with the understanding of grouping techniques increasing from an average of 40.0 to 96.0 in the post-test. The conclusion of this PkM indicates that psychomotor simulation training has a drastic impact on emergency preparedness.